Econometric methods - Johnston, J. (New York, McGraw-Hill, 1971)
This edition cover the main topics in the rapid development of Econometrics since the first edition appeared in 1963.
Includes bibliographical references.
rpm 19/07/2017
Loans
Keywords: Econometrics; Mathematical statistics